Posouzení informačního sytému a návrh změn pro UXA spol. s r.o. - Hruška, Milan (Vysoké učení technické v Brně. Fakulta podnikatelská, 2016)
Náplní této bakalářské práce je analýza informačního systému. Nalézt části systému, které je vhodné zefektivnit. První část práce je zaměřena na teoretická východiska zahrnující objasnění pojmů jako je informační systém, datové modely, EPC diagram, MS Access, metoda hodnocení HOS 8 a SWOT analýza. Teoretické poznatky slouží jako základní kámen pro zpracování analytické části a tvorbu navrženého řešení. Analytická část se zabývá charakteristikou společnosti a analyzuje používaný informační systém, slouží jako podklad k vypracování závěrečné části práce. Poslední část práce obsahuje návrhy změn, které přispějí ke zlepšení efektivity informačního systému a tím i celé společnosti.

The purpose of this bachelor’s thesis is to analyse an information system, specifically to find the parts of the system which should be made more effective. First part of the paper is focused on the theoretical basis encompassing the clarification of terms such as information system, data models, EPC diagram, MS Access, HOS 8 method, and SWOT analysis. The theoretical basis serves as a foundation stone for the analytical part and for creation of the suggested solution. The analytical part deals with the basic characterization of the company and analyses its current information system and then serves as a base for devising the final part of the paper. The last part includes the proposal of the changes which will contribute to the improvement of effectivity of the information system and therefore the whole company.
Information System Assessment and Proposal for ICT Modification for UXA spol. s r.o.
Keywords: Informace; data; databáze; informační systém; návrh informačního systému; HOS 8; SWOT analýza; MS Access; výrobní kalkulace.; Information; data; database; information system; design of an information system; HOS 8; SWOT analysis; MS Access; production calculation.